Interchange Injections at Saturn: Statistical Survey of Energetic H+ Sudden Flux Intensifications. Issue 6 (15th June 2018) - Azari, Abigail R.; Liemohn, Michael W.; Jia, Xianzhe; Thomsen, Michelle F.; Mitchell, Donald G.; Sergis, Nick; Rymer, Abigail M.; Hospodarsky, George B.; Paranicas, Christopher; Vandegriff, Jon
Abstract: We present a statistical study of interchange injections in Saturn's inner and middle magnetosphere focusing on the dependence of occurrence rate and properties on radial distance, partial pressure, and local time distribution. Events are evaluated from over the entirety of the Cassini mission's equatorial orbits between 2005 and 2016. We identified interchange events from CHarge Energy Mass Spectrometer (CHEMS) H + data using a trained and tested automated algorithm, which has been compared with manual event identification for optimization. We provide estimates of interchange based on intensity, which we use to investigate current inconsistencies in local time occurrence rates. This represents the first automated detection method of interchange, estimation of injection event intensity, and comparison between interchange injection survey results. We find that the peak rates of interchange occur between 7 and 9 Saturn radii and that this range coincides with the most intense events as defined by H + partial particle pressure. We determine that nightside occurrence dominates as compared to the dayside injection rate, supporting the hypothesis of an inversely dependent instability growth rate on local Pedersen ionospheric conductivity. Additionally, we observe a slight preference for intense events on the dawnside, supporting a triggering mechanism related to large‐scale injections from downtail reconnection. Our observed local time dependence paints a dynamic picture of interchange triggering due to both the large‐scale injection‐driven process and ionospheric conductivity. Plain Language Summary: Studying high‐energy particles around magnetized planets is essential to understanding processes behind mass transport in planetary systems. Saturn's magnetic environment, or magnetosphere, is sourced from a large amount of low‐energy water particles from Enceladus, a moon of Saturn. Saturn's magnetosphere also undergoes large rotational forces from Saturn's short day and massive size. The rotational forces and dense internal mass source drive interchange injections, or the injection of high‐energy particles closer to the planet as low‐energy water particles from the inner magnetosphere are transported outward. There have been many strides toward understanding the occurrence rates of interchange injections, but it is still unknown how interchange events are triggered. We present a computational method to identify and rank interchange injections using high‐energy particle fluxes from the Cassini mission to Saturn. These events have never been identified computationally, and the resulting database is now publically available. We find that the peak rates of interchange occur between 7 and 9 Saturn radii and that this range coincides with the highest intensity events. We also find that interchange occurrence rates peak on the nightside of Saturn. Through this study, we identify the potential mechanisms behind interchange events and advance our understanding of mass transport around planets. Key Points: We developed a novel classification and identification algorithm for interchange injection based on Cassini CHEMS 3–220 keV H + energetic ions Radial occurrence rates and maximum partial H + pressure in interchange peaked between 7 and 9 Saturn radii for all intensity categories Occurrence rates peak on the nightside (1800–0600 LT) as compared to the dayside (0600–1800 LT)